Effect of long-term conservation tillage management on microbial diversity under Mediterranean rainfed conditions - Ibáñez, Ana; Sombrero, Aurora; Santiago-Pajón, Arturo; Santiago-Calvo, Yolanda; Asensio-S.-Manzanera, M. Carmen (Soil & tillage research, 2024)
Conservation Agriculture has been the subject of numerous studies for decades. However, its impact on the soil microbial community has often been overlooked. Recent studies have shed light on the changes in soil bacterial composition resulting from modifications in tillage practices, particularly when compared to conventional tillage methods. However, there is a lack of soil microbial community analysis conducted under conservation tillage and rainfed conditions in the Mediterranean basin. A metataxonomic approach was employed to assess the influence of 19 years (2004–2022) of minimum tillage (MT) and no-till (NT) practices, along with crop rotation, on the soil bacterial community at upper layers (15 cm depth). This field study involved three different seasonal moments throughout the year. Results revealed that both sampling time and tillage management significantly influenced the structure of the bacterial community, whereas no effect was observed due to the crop. May showed a higher taxonomic diversity than July and December, showing differences in some o fthe most abundant phyla, such as Actinobacteria, Firmicutes and Proteobacteria. On the other hand, the long-term application of NT was found to lead to a significant decrease in bacterial diversity, with lower abundances of the phyla Chloroflexi, Gemmatimonadetes, and Armatimonadota, as well as an increase in k-strategist bacteria compared to MT. However, no significant effect on alpha diversity was observed as a result of tillage. no variations in phyla composition were observed attributable to crop, as the primary distinctions were identified among legume crops, which were associated with different sampling times. Therefore, our conclusion is that over this period, NT did not promote microbial diversity in the upper soil layers, despite notable shifts in bacterial composition occurring across seasonal time points in both tillage management systems.